2019
DOI: 10.3390/ijms20225734
|View full text |Cite
|
Sign up to set email alerts
|

A Single Synonymous Variant (c.354G>A [p.P118P]) in ADAMTS13 Confers Enhanced Specific Activity

Abstract: Synonymous variants within coding regions may influence protein expression and function. We have previously reported increased protein expression levels ex vivo (~120% in comparison to wild-type) from a synonymous polymorphism variant, c.354G>A [p.P118P], of the ADAMTS13 gene, encoding a plasma protease responsible for von Willebrand Factor (VWF) degradation. In the current study, we investigated the potential mechanism(s) behind the increased protein expression levels from this variant and its effect on ADAMT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…Codon usage in KRAS, which encodes an oncogenic Ras GTPase family member, was shown to regulate the expression and protein structure of KRAS protein when expressed in human cells [22,23]. More recently, codon usage optimization of the coagulation factor IX and a single SNP of the ADAMTS13 has been shown to affect protein folding or activity [82,83]. Together, these studies firmly established the universal role of codon usage in protein folding in both prokaryotes and eukaryotes.…”
Section: The Role Of Codon Usage In Protein Foldingmentioning
confidence: 89%
“…Codon usage in KRAS, which encodes an oncogenic Ras GTPase family member, was shown to regulate the expression and protein structure of KRAS protein when expressed in human cells [22,23]. More recently, codon usage optimization of the coagulation factor IX and a single SNP of the ADAMTS13 has been shown to affect protein folding or activity [82,83]. Together, these studies firmly established the universal role of codon usage in protein folding in both prokaryotes and eukaryotes.…”
Section: The Role Of Codon Usage In Protein Foldingmentioning
confidence: 89%
“…It became clear that synonymous codon changes could also cause the development of human disease [149][150][151][152][153][154] and potentially affect safety and efficacy of the recombinant/therapeutic proteins [155][156][157]. Surprisingly, it was also found that even a single synonymous mutation can be deleterious to protein folding and function [141,152,158].…”
Section: Codon Usage Code For Protein Folding In the Cell: Importancementioning
confidence: 99%
“…In eukaryotes, a synonymous single-nucleotide polymorphism of the human MDR1 gene was previously shown to cause altered protein activity of the MDR1 protein transiently overexpressed in human cells, suggesting the involvement of codon usage in eukaryotic protein folding ( 39 ). More recently, codon usage was also shown to influence protein activity and/or structures of several other human proteins ( 28 , 45 , 48 50 ). However, those previous studies relied on protein overexpression, which could also influence protein folding in cells, and the degree of impact of codon usage on protein structure/function was often modest.…”
Section: Introductionmentioning
confidence: 99%